Experimentally induced community assembly of polypores reveals the importance of both environmental filtering and assembly history. (October 2019) - Norberg, Anna; Halme, Panu; Kotiaho, Janne S.; Toivanen, Tero; Ovaskainen, Otso
Abstract: The community assembly of wood-inhabiting fungi follows a successional pathway, with newly emerging resource patches being colonised by pioneer species, followed by those specialised on later stages of decay. The primary coloniser species have been suggested to strongly influence the assembly of the later-arriving community. We created an artificial resource pulse and studied the assembly of polypores over an 11 yr period to ask how the identities of the colonising species depend on the environmental characteristics and the assembly history of the dead wood unit. Our results support the view that community assembly in fungi is a highly stochastic process, as even detailed description of the characteristics of dead wood (host tree species, size, decay class of the resource unit, its bark cover and how sunken it is to the ground) and the prior community structure provided only limited predictive power on the newly colonising species. Yet, we identified distinct links between primary and secondary colonising species and showed how the spatial aggregation of dead wood had a great impact on the community assembly.